Spiritualitas Sosial Yang Bersumber dari Kristus - Melan Melan; Obertina Gomor; Yohanes Yappo; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
As time goes by, human life requires effective and efficient spiritual practices. In Christ's teachings, love is the main value that must be applied in social relationships. This love includes understanding, empathy, and concern for others. Christ also taught the importance of forgiveness, both giving and receiving forgiveness, to repair broken relationships. Apart from that, the value of loyalty is also emphasized in Christ's teachings. This loyalty involves a commitment to mutual support and maintaining strong relationships. Christ also taught the importance of brotherhood, where all people are considered brothers and sisters in the faith, regardless of social or cultural differences. Social justice is also an important part of Christ's teachings. Christ taught us to be fair in treating others and to give equal rights to all people, regardless of their background or social status.